1995
DOI: 10.1128/aac.39.2.513
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and tissue penetration of the new fluoroquinolone grepafloxacin

Abstract: A single 400-mg oral dose of grepafloxacin (OPC-17116) was given to each of six healthy male volunteers, and the concentrations of the drug in plasma, cantharides-induced inflammatory fluid, and urine were measured over the subsequent 12 h. The mean peak concentration in plasma of 1.5 g/ml was attained at a mean time of 2.0 h postdose. The mean peak concentration in inflammatory fluid of 1.1 g/ml was attained at a mean time of 4.8 h postdose. The mean elimination half-life in plasma was 5.2 h, and that in infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(12 citation statements)
references
References 10 publications
2
9
0
1
Order By: Relevance
“…The model differs from previous population kinetic models in that not only the partition coefficient but also passive diffusion and active trans- We found a high volume of distribution in the peripheral (tissue) compartment. This is consistent with previous studies (8,13,31) and predictions based on the high lipophilicity of the drug. The average partition coefficient is close to the value obtained by descriptive analysis (16.9 versus 16.0%) (14).…”
Section: Discussionsupporting
confidence: 82%
“…The model differs from previous population kinetic models in that not only the partition coefficient but also passive diffusion and active trans- We found a high volume of distribution in the peripheral (tissue) compartment. This is consistent with previous studies (8,13,31) and predictions based on the high lipophilicity of the drug. The average partition coefficient is close to the value obtained by descriptive analysis (16.9 versus 16.0%) (14).…”
Section: Discussionsupporting
confidence: 82%
“…[14][15][16][17][18] Pharmacokinetic studies suggested that grepafloxacin was better distributed in tissues than other fluoroquinolone antibiotics, especially in lung 19,20 and in alveolar macrophages. 13 Thus, grepafloxacin is expected to be useful against intracellular pathogens that cause respiratory infections, such as Legionella, Chlamydia, and Mycobacterium species.…”
Section: Discussionmentioning
confidence: 99%
“…In an early study using grepafloxacin, six healthy male volunteers (mean age 28 years, mean weight 73 kg) were given a single oral dose of grepafloxacin, 400 mg [2]. The levels of the drug were measured in plasma, in urine and in a cantharidin‐induced inflammatory fluid model.…”
Section: Pharmacokineticsmentioning
confidence: 99%